Indicators of Tribal Identity in Aotearoa/New Zealand - Milroy, Wharehuia (Te Kaharoa, 2008)
This article offers a penetrating analysis of issues surrounding tribal identity. Themes of language, leadership, guardianship, tradition, whanau, whakapapa, and a sense of those things that combine to give, in this case, Tuhoe, its identity, are considered.